Strategi Kepala Madrasah dalam Menanamkan Nilai Humanis Religius kepada Siswa Madrasah Aliyah - Utami, Lia Dwi; Khoiriyah, Iis Siti (Al-Liqo: Jurnal Pendidikan Islam, 2024)
The aim of the research is to explain the strategy related to the headmaster of the madrasa in instilling religious humanist values ​​in Madrasah Aliyah Ibnul Qoyyim Yogyakarta students. The cultivation of religious humanist values ​​is carried out to form students who have good morals and noble character. When morals and morals are instilled in students, it becomes an important first step towards a smarter future for Indonesia. This research uses field research with a descriptive approach. The results of the research strategy in an effort to instill religious humanist values ​​at the Ibnul Qoyyim Yogyakarta Madrasah have been maximized, starting with giving an example by having joint prayers, attendance/fingerprints, and dress codes, then the habituation is carried out, namely starting from apples every week, activities garbage banks, congregational midday prayers, dhuha prayers, recitations of the Koran, Infaq, then the correction of supervision and the existence of punishments are able to create school areas that are able to create religious humanism values, because every policy made certainly does not escape from the principles of the Qur'an an and Hadith.